PENGENALAN PRAKTIKUM SAINS DARI BAHAN YANG ADA DI SEKITAR SEBAGAI SUMBER PEMBELAJARAN DARING BAGI GURU SMP NURUL FADHILAH - Sri Adelia Sari; Zainuddin Muchtar; Rini Selly; Siti Rahmah; Jasmidi Jasmidi; Moondra Zubir; Putri Faradilla; Dwy Puspita Sari (Jurnal Abdi Insani, 2023)
This community service activity focuses on dealing with partner problems, namely junior high school teachers at YP Nurul Fadhilah. The problems faced are the lack of application of material-based practicum around and teachers’ lack of knowledge and skills regarding making practicum innovations a source of online learning. A teacher is required to be able to adapt to the development of science and technology during the industrial revolution 4.0, therefore additional activities are needed to make this happen. This activity aims to increase teacher knowledge and skills in applying material-based practicum around to become an online learning resource. The method used consists of 4 stages, namely: Socialization of the introduction of practicum from nearby materials, training on making practicum into an online learning resource and assistance in the implementation of making online learning resources and evaluating results. Executors provide tools and materials, while partners prepare laptops for application training. The results obtained from this activity were that the teachers experienced improvements both in terms of knowledge and skills. Quantitatively, the teacher's ability regarding practical knowledge from surrounding materials to online learning materials increased for science teachers with an average score of 83.3 and non-science teachers with an average score of 66.43. In addition to increasing knowledge and skills, partners also produce products, namely online learning resources in the form of videos. In general, partners have produced products in good condition. Conclusion: This PKM activity increases partners' knowledge of using local materials. This activity also adds to teachers' skills in creating online learning resources.